Discussion on the concept of technology and technology transfer in the prevailing Technology Transfer Law - Anh, Nguyen Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The paper "The prevailing Law on Technology Transfer needs to be amended" by author Do Thi Bich Ngoc, Ministry of Science and Technology published in the Vietnam Science and Technology Journal, No.22/2014, had pointed out some inadequacies of the prevailing Law on Technology Transfer and suggested direction for further amendments and revisions. This paper below is a continued effort to comment on irrelevant points of the Law on Technology Transfer, focusing mostly on the concept of technology, technology transfer as specified in the Law, and propose direction for readers to further exchange discussion with a view to contributing together to the improvement of the Law. Code: 15022501